Histopathologic study of endometrium in cases of abnormal uterine bleeding (Journal of Pathology of Nepal, 2023)
Background: Abnormal uterine bleeding is one of the most common presenting symptoms among women visiting the gynecology outpatient department. Sonography and endometrial biopsy are the usual methods of evaluation; rarely, invasive procedures like hysteroscopy may be needed. Endometrial sampling can be used as a first step in the evaluation. This study was done to analyze the histopathology of the endometrium and to evaluate the causes of abnormal uterine bleeding.Materials and Methods: Endometrial samples were obtained using dilation and curettage from 50 women presenting to the gynaecology outpatient department with abnormal uterine bleeding symptoms in a medical college hospital.Results: Among the 50 cases, 21 were found to have endometrial hyperplasia (72.4%); 24 were diagnosed to have an organic lesion (48%). The endometrium was found to be in the proliferative phase in the majority of the cases (40%). The most common age group was 31-40 years and simple cystic hyperplasia was the commonest endometrial pattern. Single-parity women were most commonly affected and they showed a secretory endometrium under microscopy.Conclusions: Endometrial sampling should be carried out in every patient with abnormal uterine bleeding to study the histopathology of the endometrium and to evaluate the causes of the disease.